Optimization of the condition of phytosterol extraction conditions from microalgae nannochloropsis using ethanol of different purity levels - Fithriani, D; Nurhayati, - (Journal of Bio-Science, 2019)
Phytosterols are plant sterols, included in secondary metabolite compounds and have broad benefits in the health field. This study aims to observe the effect of ethanol solvency purity, time of extraction on phytosterol content. The extraction was carried out by saponification using a 7.5% KOH solution in ethanol. The variations in extraction time are 1, 2, 3, and 4 hours. Ethanol used varies purity levels, i.e technical 70%, technical 96%, and pure analysis. The variations in maceration time are 1, 2 and 3 days. The results showed that all ethanol solvents with different purity levels resulted in the highest crude phytosterol under long duration of 1 hour extraction time. The ethanol purity rate had a significant effect on the yield of phytosterol produced, i.e., 70% technical, 96% technical, and pure analysis consume 0.4%, 1.63% and 4.19% crude phytosterol, respectively. J. bio-sci. 27: 143-148, 2019